Demographics of Physician Associates (PAs) in Obstetrics and Gynecology: Where They Work and How They Compare to Other PAs - Melissa A. Rodriguez; Roderick S. Hooker; Kasey K. Puckett; Andrzej Kozikowski (Obstetrics and Gynecology International)
As of 2020, maternal and infant health in the US has worsened. At the same time, the number of health professionals available to manage female health issues is changing; the number of physicians in obstetrics and gynecology (Ob-Gyn) and midwives is decreasing, whereas the number of Ob-Gyn physician associates (PAs) is growing. We analyzed PAs practicing in the Ob-Gyn discipline, drawing on the PA Professional Profile, a database maintained by the National Commission on Certification of PAs. In 2021, there were 1,322 Ob-Gyn PAs (1.2% of all clinically active PAs). This health profession has grown by 66.9% since 2013, when only 792 PAs practiced in this specialty. As of 2021, their median age was 38, and 98.0% were female (70.1% of all PAs were female). The practice setting was between office (54.7%) and hospital (34.0%) employment, with 11.3% described as “other.” In 2021, the median annual income of Ob-Gyn PAs was $105,000. With the reduction of obstetrician-gynecologists, the relative growth of PAs in this area of medicine and surgery is a natural part of the solution to the projected obstetrical physician deficit.